Prognostic Value of Initial Assessment of Residual Hypoventilation Using Nocturnal Capnography in Mechanically Ventilated Neuromuscular Patients: A 5-Year Follow-up Study - Ogna, Adam; Nardi, Julie; Prigent, Helene; Quera Salva, Maria-Antonia; Chaffaut, Cendrine; Lamothe, Laure; Chevret, Sylvie; Annane, Djillali; Orlikowski, David; Lofaso, Frederic (Frontiers in Medicine, 2016)
Background Restrictive respiratory failure is a major cause of morbidity and mortality in neuromuscular diseases (NMD). Home mechanical ventilation (HMV) is used to treat hypoventilation, and its efficiency is mostly assessed by daytime blood gases or nocturnal oxygen saturation monitoring (SpO2). Non-invasive transcutaneous measure of CO2 (TcCO2) allows to directly assess nocturnal hypercapnia and to detect residual hypoventilation with a higher sensitivity than SpO2. We aimed to compare the prognostic value of nocturnal SpO2 and TcCO2 in ventilated adult NMD patients. Methods All consecutive capno-oximetries performed between 2010 and 2011 in ventilated adult NMD patients were analyzed retrospectively. Concomitant blood gas analysis and lung function data were collected. Patients on oxygen therapy were excluded. Nocturnal hypoxemia and hypercapnia (using four different definitions) at baseline were compared in their ability to predict mortality and respiratory events requiring ICU admission during follow-up. Results Data from 55 patients were analyzed (median age 28 [interquartile range: 25–36.5] years; 71% Duchenne muscular dystrophy; vital capacity 12 [7–27]% of predicted; 51% tracheostomy). Capno-oxymetry showed hypoxemia in 14.5% and hypercapnia in 12.7–41.8%, according to the used definition. Over a follow-up lasting up to 5 years (median 4.0 [3.6–4.5] years), we observed 12 deaths and 20 respiratory events requiring ICU admission. Hypercapnia was significantly associated with the study outcomes, with TcCO2 > 49 mmHg during ≥10% of the time being the best definition, while hypoxemia was not. Conclusion Our data show for the first time that residual hypoventilation, assessed by capnometry, is significantly associated with negative outcomes in adult ventilated NMD patients, while oximetry is not. Accordingly, we suggest capnometry to be included in the systematic assessment of HMV efficiency in NMD patients. ClinicalTrials.gov Identifier NCT02551406.